Factors Influencing the Intention to Use E-Wallet Payment Among Millennials and Generation Z in Malaysia - Kia Hui Gan; Hui Ling Lim; Ke Shan Choo; Jes Yee Chong; Jing En Chong; Xin Yi Chong; Kai Wen Choong; A. J. Ali; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2025)
The monetary climate has evolved due to the rapid advancement of digital payment systems, and Touch ‘n Go is one of the contactless smart card systems that is commonly used to conduct transactions, especially among younger generations. Touch ‘n Go is the foundation of the digital revolution within Malaysia’s mobility ecosystem, creating an enjoyable shopping experience for millions of Malaysians. Thus, this study investigates the factors influencing Millennials and Generation Z's intention to use e-wallets. The research focuses on four key variables: perceived security, perceived usefulness, consumer’s attitude, and social influence. Data was collected through a survey of 150 Millennials and Generation Z respondents and the impact of these factors on the intention to use e-wallets was analysed using quantitative methods. The findings show that perceived usefulness and consumer attitude significantly drive Touch ’n Go eWallet adoption, emphasizing functionality and user experience. However, perceived security and social influence had no significant impact on usage intention. The study offers insights for digital wallet providers and legislators looking to boost the adoption rate of digital payment systems in Malaysia.